Medical writing in the Russian Federation: Promises and pitfalls. (1st June 2013) - Davydova, Anna
Abstract : More and more clinical studies are taking place in Russia, making it an attractive market for medical writing. In 2011, the Ministry of Healthcare of the Russian Federation approved over 550 new clinical studies of all types, a 16% increase over the previous year. Currently, the Russian government is making huge investments in its infrastructure for drug development. Demand for medical writing is high in the rapidly growing sector of biotechnology in Russia. Because there are some differences in local requirements compared to the EU or USA, many specific regulatory aspects have to be considered by medical writers in Russia.